Co-application of controlled-release urea and a superabsorbent polymer to improve nitrogen and water use in maize. Issue 7 (7th June 2022) - Fan, Zhen; Tian, Xiaofei; Zhai, Sheng; Liu, Zhongliang; Chu, Pengfei; Li, Chengliang; Sun, Shuchen; Li, Tingting
ABSTRACT: A field experiment consisted of two types of N fertilizer, controlled release urea (CRU) and normal urea (U), in combination with three SAP application rates (0, 45 and 90 kg ha −1 ) in a split-plot design was conducted in 2018 and 2019. The successive release of N from polymer-coated urea corresponded well to the N requirements of maize growth. The NO3 − -N and NH4 + -N contents in the 0–20 cm soil layer were enhanced at the jointing and 12 leaf collar stages, and the leaching of soil NO3 − -N was reduced by using CRU. The application of superabsorbent polymer (SAP) increased soil water stock, decreased evapotranspiration, and enhanced water use efficiency (WUE) and nitrogen use efficiency (NUE). The combined application of CRU and 90 kg ha −1 SAP achieved maximal maize yield, WUE, NUE, and net income values that were 0.8–32.9%, 0.2–37.4%, 4.1–13.1%, and 2.8–42.1%, respectively, higher than those of other treatments. These results demonstrate that the co-application of CRU and 90 kg ha −1 SAP is an effective practice that enhances the water and N utilization of maize and could potentially have wide application on the North China Plain.